Socioeconomic Impact of Limestone Mining on Local Communities in the Khumnoh Area, Kashmir, India - Gazala Yousuf Mir (RADJA PUBLIKA, 2025)
Limestone mining, while pivotal to industrialization and infrastructure expansion, often begets a paradoxical coexistence of economic promise and socio-environmental adversity—particularly in ecologically sensitive and socially fragile landscapes. This study interrogates the multifaceted implications of limestone extraction on the local communities of Khumnoh, situated within the tectonically active and resource-rich belt of South Kashmir. Despite burgeoning industrial interest in the region, scholarly inquiry into the sociological and economic reverberations of mineral extraction remains conspicuously limited. This research endeavors to bridge this epistemic lacuna by conducting an in-depth, community-centric investigation into the socioeconomic ramifications of limestone mining in the aforementioned locale. Employing a robust mixed-methods framework, the study integrates quantitative data from 100 structured household surveys with qualitative insights derived from 10 semi-structured interviews involving diverse community stakeholders—including miners, traders, educators, healthcare workers, and governance representatives. Stratified random sampling ensured representational integrity, while thematic analysis of narrative accounts augmented the statistical findings, thereby affording a comprehensive evaluative lens. The analysis focused on key dimensions such as livelihood diversification, income generation, public health, environmental degradation, gendered access to mining benefits, and infrastructural evolution. The findings reveal an ambivalent reality: while a notable segment of the population has experienced marginal economic uplift through mining-related employment and trade linkages, the majority remains either unengaged or inadequately compensated. Dust proliferation, water resource vulnerability, and respiratory ailments were recurrent environmental grievances, compounded by a palpable deficit in corporate transparency and public participation in decision-making processes. Furthermore, infrastructure benefits were largely confined to transport routes, with limited investment in healthcare, education, or gender-inclusive development. The study concludes that while limestone mining in Khumnoh does contribute to regional economic circuits, it does so in a manner that is neither equitably inclusive nor environmentally sustainable. Absent proactive regulatory oversight and participatory governance, the current trajectory of extractive expansion portends long-term socioecological dislocation. It is thus imperative to recalibrate mining operations through community engagement mechanisms, environmental safeguards, and targeted corporate social responsibility (CSR) interventions. The study not only elucidates the nuanced interplay between resource extraction and human development in peripheral regions but also offers a replicable analytical paradigm for evaluating the social license to operate in similar geoeconomic contexts.